Pengaruh Passive Stretching Exercise Terhadap Perubahan Fleksibilitas Hamstring Pada Kasus Osteoartritis Genu Di Rumah Sakit Dr.Soepraoen Kota Malang - Wahyu Oni Kurniawan; Angria Pradita; Rachma Putri Kasimbara; Nurul Halimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Flexibility is the ability of a muscle to be stretched as much as possible so that the body can move freely without any discomfort/ pain. The purpose of this study was to determine the effect of passive stretching exercise on changes in hamstring flexibility in patients with genu osteoarthritis at dr. Soepraoen Malang HospitalMethods: This study used a pre-experimental design with the design used in this study was one group pretest-posttest. This study used genu osteoarthritis patients at dr. Soepraoen Malang Hospital, as many as 20 patients, using a purposive sampling method using Wilcoxon Test data analysisResults: The results showed that there was an effect of passive stretching exercise on changes in hamstring flexibility in genu osteoarthritis patients at dr. Soepraoen Malang Hospital , the Wilcoxon Test's significance value is 0.002<α (α=0.05)Conclusion: 1. The average flexibility of the hamstring muscles in genu osteoarthritis patients before giving passive stretching exercise was 15, with a minimum value of 13 and a maximum value of 18 and a standard deviation value of 2.026. 2. The average flexibility of the hamstring muscles in patients with genu osteoarthritis after giving passive stretching exercise was 15.85 with a minimum value of 13 and a maximum value of 18 and a standard deviation value of 2.033. 3. There is an effect of passive stretching exercise on changes in hamstring flexibility in patients with genu osteoarthritis, which can be shown that the significance value of the Wilcoxon Test is 0.002 <α (α = 0.05)